Discover Potential of Community-based Tourism in Non Nuoc Cao Bang UNESCO Global Geo-park, Vietnam - Cao Thi Thanh Phuong (Randwick International of Social Science Journal, 2022)
The poetic landscape, majestic mountains and the system of waterfalls, interesting rivers and lakes,... create a picture of a “fairy landscape” of the Non Nuoc UNESCO Cao Bang region. The beautiful scenery here is also associated with the global geo-historical values, the values ​​of biodiversity, the diversity of national identities and the richness of culture and history with many national-level cultural and historical relics. National, special country has created for the area of Non Nuoc Cao Bang Geopark a special attraction for domestic and foreign tourists. The article focuses on exploring the natural and human potential of the Non Nuoc Cao Bang Global Geopark area as well as the tourism results achieved in the past time to serve as a basis for proposing solutions to develop the area develop the type of community-based tourism for the study area.